Irritable Hip as the Inaugural Symptom for Neuroblastoma - Sara Alves da Silva; Jorge Mendes; João Carvalho; Hélder Nogueira; Helena Barroca; Margarida Fernandes; Edite Tomás (Case Reports in Orthopedics)
Case Report. A four-year-old girl presented with fever and a painful limp in the left hip. Pain characteristics and anemia detected in the blood analyses were the first warning signs that the hip process was not standard. Although the primary suspicion was of septic arthritis, a CT scan of the abdomen revealed an adrenal neuroblastoma. Conclusion. The presenting signs of neuroblastoma are commonly atypical. About 25% of presentations are orthopedic and mimic a variety of severe orthopedic conditions. The most important clinical dilemma is distinguishing benign and self-limiting disorders from septic or malignant processes.